The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/lno.11651
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nitrogen is changing the East China and Yellow seas from being N deficient to being P deficient

Abstract: Addition of the increased anthropogenic nitrogen (NO x and NH y) emitted from northeast Asian countries to the Yellow and East China seas and coastal waters around Korea has resulted in an unparalleled increase in the nitrate (N) concentration relative to the phosphate (P) and silicate (Si) concentrations in the upper ocean. We found that for the Yellow Sea the increase in N over P was largely explained by increased atmospheric nitrogen deposition, whereas for the northern East China Sea, downstream of the Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…In this study, we first observed that cryptophytes replaced diatoms in the NECS and were the dominant species in autumn and winter 2020. This recent pattern could be related to the overall nutrient transitions from N-deficient to P-deficient environmental conditions caused by anthropogenic nitrogen inputs in the NECS observed from 1980 to 2016 (Moon et al, 2021). Our result showed that the P-limitation indicated by ExN > 0 µM existed in all seasons from 2018 to 2020 (Table 3).…”
Section: Diatoms and Cryptophytessupporting
confidence: 50%
See 2 more Smart Citations
“…In this study, we first observed that cryptophytes replaced diatoms in the NECS and were the dominant species in autumn and winter 2020. This recent pattern could be related to the overall nutrient transitions from N-deficient to P-deficient environmental conditions caused by anthropogenic nitrogen inputs in the NECS observed from 1980 to 2016 (Moon et al, 2021). Our result showed that the P-limitation indicated by ExN > 0 µM existed in all seasons from 2018 to 2020 (Table 3).…”
Section: Diatoms and Cryptophytessupporting
confidence: 50%
“…High DIN concentrations and DIP-limited environments in 2020 caused dinoflagellates and small phytoplankton groups such as cryptophytes, cyanobacteria, and prymnesiophytes to be more competitive than diatoms. In particular, cryptophytes were first observed as the dominant species in autumn/winter 2020 in the NECS, which could be related to increasing anthropogenic nitrogen inputs in the study area (Moon et al, 2021). Moreover, dinoflagellates, which predominated in spring 2020, tended to bloom at low phosphorus and high ExN conditions compared with diatoms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Sedimentation rate, another well‐established control of OC burial in coastal systems (e.g., Bao et al., 2018; Blair & Aller, 2012; Cui, Bianchi, Jaeger, et al., 2016), has been altered by many changes in the Anthropocene such as land‐use, precipitation gradients, eutrophication, and damming. In fact, the Eastern China Marginal Seas (ECMS), which has historically been fed by some of the most sediment‐rich rivers in the world, has been disproportionality altered by such human activities (e.g., Moon et al., 2020; Wu et al., 2020) ‐ due to profound economic growth in the region (He et al., 2014). The ECMS provides prolific gradients of change for exploration, and thus offers a unique set of natural laboratories to investigate these questions.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the increasing frequency of K. mikimotoi blooms aligns with the varying nutrient structure in the coastal waters of East Asia in recent years. Due to the rapid development of the human population and the concomitant increase in industrial and agricultural activities, the unbalanced input of nitrogen (N) and phosphorus (P) into coastal waters has caused an obvious increase in the N:P ratio in East Asia [ 21 , 22 ]. Phytoplankton normally suffer P deficiency in late spring and summer in this area [ 21 ].…”
Section: Introductionmentioning
confidence: 99%